2021
DOI: 10.3390/met11121916
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Cooling in Finishing Turning of Haynes 282 Using Carbide Tools: Haynes 282 and Inconel 718 Comparison

Abstract: Despite the interest of industry in nickel-based superalloys and its main features (high temperatures resistance, hardness, low thermal conductivity, among others), even today they are still materials that are difficult to cut. Cutting tools withstand both high pressures and temperatures highly localized at the cutting area because of the elevated work hardening of the alloy and the problems for the cutting fluid to access the region, with the consequent strong tool wear. The use of cutting fluids at high pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The results showed that under optimal coolant pressure, adhesion wear can be minimized. Díaz-Álvarez et al [22] studied the finishing turning of Haynes 282 under high-pressure cooling and found that under high-pressure cooling, when the cutting speed is 50 m/min and the feed is 0.1 mm/r, the workpiece can obtain the best surface finishes. Wang et al [23] found through experimental research on cutting the superalloy GH4169 with PCBN tools under high-pressure cooling that high-pressure cooling can reduce chip length, curl radius, and chip width.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that under optimal coolant pressure, adhesion wear can be minimized. Díaz-Álvarez et al [22] studied the finishing turning of Haynes 282 under high-pressure cooling and found that under high-pressure cooling, when the cutting speed is 50 m/min and the feed is 0.1 mm/r, the workpiece can obtain the best surface finishes. Wang et al [23] found through experimental research on cutting the superalloy GH4169 with PCBN tools under high-pressure cooling that high-pressure cooling can reduce chip length, curl radius, and chip width.…”
Section: Introductionmentioning
confidence: 99%
“…Machining of hard-to-cut alloys such as titanium alloys and nickel-based super alloys is a challenging and troublesome task owing to the generation of higher cutting temperatures, as well as a difficulty in maintaining dimensional accuracy and minimizing surface roughness [ 2 , 3 , 4 , 5 , 6 ]. To machine the nickel-based super alloys effectively nontraditional machining techniques should be applied or at least machining variables and their range should be carefully selected [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%